Integrating Network Pharmacology and Molecular Docking to Investigate Boerhavia diffusa for Pancreatic Cancer Treatment - Gouri Anil (International Journal of Molecular Biotechnological Research, 2024)
Objective: In this study, network pharmacology was applied to determine the therapeutic effects of the bioactive compounds of Boerhavia diffusa. Network pharmacology can unearth the underlying mechanisms between drugs and the disease targets and aids in the discovery of novel medications for complex conditions such as cancer. Methods: To predict the molecular mechanisms of action of Boerhavia diffusa in the treatment of was screened using the GeneCards database. The Venn diagram was used to identify the intersecting targets of Boerhavia diffusa and Alzheimer’s disease. The obtained target information was entered into the STRING database to construct a protein-protein interaction network. Database for Annotation, Visualization, and Integrated Discovery (DAVID) database was used to perform the GO and KEGG Pathway Enrichment analysis. Cytoscape Software was used to construct the networks, and the key targets were identified. The binding affinity of the bioactive compounds of Boerhavia diffusa with the target proteins was analyzed. PyRx, an online tool was used to perform molecular docking. It was performed using protein structures from the Protein Data Bank (PDB) Database and PubChem. BIOVIA Discovery Studio software was used to analyze the protein structure. Result: Upon performing molecular docking, the proteins AKT1, epidermal growth factor receptor (EGFR), and STAT3 have the best binding affinities with the bioactive compounds of Boerhavia diffusa. Conclusion: According to the results, the phytocompounds have potential therapeutic effects which provide insight into the theoretical basis for the investigation of the pharmacological mechanism of Boerhavia diffusa. Alzheimer’s disease using network pharmacology, the phytocompounds were obtained from the IMPPAT database. Target information for the phytocompounds and Alzheimer’s disease
Keywords: AKT1; Boerhavia diffusa; EGFR; Pancreatic cancer; STAT3; molecular docking; network pharmacology